Use of thoracoepigastric flap in the closure of large chest wall defects after surgical treatment of locally advanced breast tumor: a case report - Rafaela Alias Horta; Fernando Antônio Mourão Valejo (Revista Brasileira de Cirurgia Plástica)
Breast cancer is the most common type of malignancy among women in Brazil and worldwide, excluding non-melanoma skin cancers. The purpose of this report is to describe the case of a patient with invasive breast carcinoma, associated with a large extent of skin involvement and nipple-areola complex, whose lesion was unchanged after neoadjuvant chemotherapy. After a Halsted mastectomy, the thoraco-epigastric flap was used to close the thoracic defect, with a favorable evolution of the patient. The use of the thoraco-epigastric flap has been described as a reliable tool because it is characterized as a technique that is easy to perform, safe and with minimal post-surgical complications.